Effect of Rewards on Employee Performance At PT Sejahtera Mandiri Lubuk Pakam - Windari, Ayu; John F. Marpaung (Journal of Economics and Business (JECOMBI), 2022)
Sejahtera Mandiri Lubuk Pakam as many as 32 people. The results of this study indicate that the independent variable, namely Reward (X), has a positive and significant effect on the dependent variable, namely Employee Performance (Y) at PT. Sejahtera Mandiri Lubuk Pakam.